A dual input single output non-isolated DC-DC converter for multiple sources electric vehicle applications - Karthikeyan, B; Sundararaju, K; Palanisamy, R; Manivasagam, R; Hossain, Ismail; Bajaj, Mohit; Shouran, Mokhtar; Abdul samad, Bdereddin; Kamel, Salah (Frontiers in Energy Research, 2022)
As the fossil fuel usage in the verge towards energy economy, it is the right time to switch over to electric vehicle because of its salient features like scalable size, no carbon emission, Silent operation and free of fuel cost. It is important to design the high voltage handling DC-DC converters with single stage conversion to integrate renewable energy resources such as solar PV and fuel cell with electric vehicle applications. This paper elucidates the design and analysis of dual input single output non-isolated cuk derived converter with high step up ratio. The proposed converter can effectively handle two different energy resources having different electrical characteristics. It makes use of one common inductor between the dual input port which reduces passive component and circuit volume. The detailed analysis with continuous current mode operation of the proposed converter is carried out in this study. The continuous current with reduced ripple in the output saves the fuel cell in terms its operating life span. The efficacy of the proposed converter is verified through simulation study and validated by constructing real time scaled down prototype model.